PEREMPUAN DAN POLITIK DI KOTA BEKASI (Telaah persperspektif Komunikasi Gender dalam Politik) - Afrina Sari (PARADIGMA : JURNAL ILMU PENGETAHUAN AGAMA, DAN BUDAYA, 2009)
This research to explain that women in Bekasi have low motivation in looking at politics and political execution which occurred in 2004 and 2009 elections. The method of writing using descriptive method by using quantitative data and research results. Analysis of data using Chi- square test (X 3). Results showed that women's political motivation in the City of Bekasi is still included in the low category, due to access a wide open yet. Not a real motivational factors associated with women's political participation, political access of women, and female representation.